P9 Paediatric prescribing: boosting the basics to reduce errors. Issue 2 (19th January 2018) - Carter, Benjamin; Ives, Rosie
Abstract : Aims: To monitor the adherence to defined quality standard of prescribing in paediatric practice within Western Sussex Hospitals NHS Foundation Trust (WSHT). By identifying deficient areas, teaching and training can then be tailored to improve performance and safety. Method: A prospective audit of paediatric drug charts was performed at both WSHT sites (St Richards and Worthing General Hospitals) once weekly over a one month period. Drug charts were excluded only if no medications were yet prescribed. 22 patients audited from St Richard's (SRH) and 34 from Worthing (WGH) were audited. Doctors within the department were aware the audit was ongoing and received feedback during the audit period about areas where improvement was needed as it would be unethical to not address prescribing issues in a timely manner. Data was collected using a standardised list of ten quality standards: Completion of all patient demographic information Whether all prescriptions are legible Completion of allergy section Appriopriate prescribing unit use Ensuring all antibiotics have a written duration and indication Any patient on oxygen must have it prescribed No unapproved generic medications names All PRN medictions should have dose and maximum frequency Prescribers need to sign and stamp prescriptions Perfection: All quality standards met. Results: The majority of quality markers were well adhered to. Criteria of legibility, allergies, appropriate unit use, PRN dose and frequency, signed and stamped were met in over 90% of the charts audited at both sites. Demographic information was consistently poorly completed over both sites (SRH=59.1%, WGH=61.8%) and antibiotic duration/indication completion was particularly poor in St Richard's Hospital (64.3% at SRH vs 95% at WGH). Very few patients audited were on oxygen (1 at SRH and 2 at WGH), only one of these patients had oxygen prescribed. Across the month 67.6% of the charts audited at Worthing achieved perfection and 50% of the charts at St Richards. Conclusion: The main conclusion drawn from this audit was that generally prescribing practises are good but that demographic completion is a particular area of weakness at both hospitals. It could be argued that these omissions are less of a safety risk than prescribing errors such as unclear drug unit but omission of the patients details at the top of the prescription page may increase the risk of a drug being prescribed on the incorrect patients' chart and lead to a significant 'wrong patient' type drug error. One of the main limitations of the audit was that as it was undertaken in summer, where patients with respiratory disease and oxygen requirement are typically fewer and accordingly only 3 patients audited were on oxygen, this limited data suggests that oxygen prescribing is another area of weakness but an increased data set is needed to validate this finding. This audit was successful at allowing us to highlight areas of poorer practice and thus where prescribing training should be targeted at both hospitals.